2020
DOI: 10.3390/jmmp4040123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Optimization Parameters of Semi-Solid Metal 6063 Aluminum Alloy from Friction Stir Welding Process Using Factorial Design Analysis

Abstract: The semi-solid-metal 6063 aluminum alloy was developed for the automotive industry. The objective of this research was to optimize parameters in friction stir welding process that can provide the highest tensile strength. The ANOVA factorial design was used to analyze rotation speed, welding speed, and tool geometry at different factor levels of experimentation. The results showed that the optimized tensile strength was 120.7 MPa from the cylindrical tool, rotation speed was from 1300 to 2100 rpm, and welding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We used 12 test examples collected from the literature [15,28,33,[71][72][73][74][75][76][77][78][79]. We identified the optimal parameters using the proposed methods and compared these with the results obtained using the D-optimal/RSM approaches on the aforementioned literature.…”
Section: The Reliability and Effectiveness Testing Of The Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used 12 test examples collected from the literature [15,28,33,[71][72][73][74][75][76][77][78][79]. We identified the optimal parameters using the proposed methods and compared these with the results obtained using the D-optimal/RSM approaches on the aforementioned literature.…”
Section: The Reliability and Effectiveness Testing Of The Proposed Methodsmentioning
confidence: 99%
“…Recent studies on the optimal process parameters for aluminum welding found that rotation speed, welding speed, shoulder diameter per pin diameter ratio, tool geometry, and surface shoulder can cause increases or decreases in the strength and number of weld line defects [25][26][27]. Several approaches for predicting the optimal aluminum welding parameters (factorial design [28], Taguchi design [29], the response surface method, a combined method [30], etc.) are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, no dendrite formation is detected in the stir and thermo-mechanically affected zones after the welding process. This defect type is not usually found in semi-solid materials 26 , 27 .
Figure 18 SEM images of the thermo-mechanically affected zone region of the samples: ( a ) threaded cylindrical pin, ( b ) conical pin, ( c ) b17, and ( d ) c12.
…”
Section: Resultsmentioning
confidence: 86%
“…The optimization of pin profile in addition to rotational and traverse speeds has been also investigated [30][31][32][33][34]. Sefene et al [30] studied multi-responses of hardness and tensile on AA6061 similar joints with a thickness of 5 mm using gray relation with Taguchi L9OA (3P:3L (1/3 of 3 3 )).…”
Section: Introductionmentioning
confidence: 99%
“…Sagheer-Abbasi et al [31] studied the tensile response of AA5052-H32 similar joints with a thickness of 1 mm using Taguchi L9OA (3P:3L (1/3 of 3 3 )). Meengam and Sillapasa [32] used a full factorial design of L64OA (3P:4L) for the optimization of AA6063 (6 mm) FSW joints. Balamurugan et al [33] studied the tensile response of dissimilar joints of AA5052-H32/AA6061-T6 with a thickness of 5 mm using Taguchi L27OA (3P:3L).…”
Section: Introductionmentioning
confidence: 99%